(untitled) (IJM: Journal of Multidisiplinary, 2025)
Bacterial meningitis is among the top ten causes of death due to infection globally and is one of the most dangerous infections in children. Therefore, proper and high-quality care for children with bacterial meningitis is essential. This case study aims to provide nursing care for patient Z with bacterial meningitis in the PICU of Dr. Zainoel Abidin Regional General Hospital, Banda Aceh. The case study method was applied to one pediatric patient and is presented based on the nursing care process. In the case of patient Z, several nursing problems were identified, including impaired gas exchange, decreased intracranial adaptive capacity, ineffective airway clearance, nutritional deficit, and risk of injury. Nursing care provided to patient Z included monitoring gas exchange disturbances, managing increased intracranial pressure, intracranial pressure monitoring, hyperthermia management, nutritional management, providing enteral feeding, monitoring vital signs, administering intravenous medications, seizure management, and seizure prevention. The outcomes of the nursing care for patient Z over three days indicate that further interventions and monitoring are required in the PICU. The results of this scientific work are expected to serve as a basis for developing nursing care management and assisting nurses in improving patient satisfaction with the nursing care provided.